INCORPORATING ISLAMIC VALUES AND SHARIAH COMPLIANCE ON MALAYSIAN STANDARD RELATED TO FOOD INDUSTRY - Dahlan, Hadi Akbar; Alina, A.R.; Muhammad, S.K.; Yusop, M.H.M. (Online Journal of Research in Islamic Studies, 2014)
Shariah and Islamic Value are often known but not fully understood. The Malaysian Standard (MS) is a standard developed and published by Standards of Malaysia. These standard set in motion the policy and values in the industry. Regarding the food industry, there are three MS that is certifiable: MS 1480: Food Safety According To Hazard Analysis And Critical Control Point (HACCP) System, MS 1500: Halal Food – Production, Preparation, Handling And Storage – General Guidelines, and MS 1514 - Good Manufacturing Practice (GMP) For Food. Although practiced and recognized globally, the standards are without loophole. This enable industries exploitation for selfish means. It is believe incorporating Shariah and Islamic Value would greatly benefit the community and set the Food Industry toward a higher excellence of Halal Food Quality and safety production. This paper will briefly introduce Shariah and the Islamic Value Framework as well as the three standards regarding it requirements in its implementation